Unintended pregnancy in midlife women: a narrative review of prevention frameworks and health system challenges in Indonesia - Sardjana Sardjana; Mahesa Paranadipa Maikel; Hari Hendarto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Unintended pregnancy among midlife women (approximately 40–55 years) remains marginal within reproductive health research, despite persistent fertility during the perimenopausal transition and elevated maternal health risks at older ages. This narrative review synthesises peer-reviewed empirical studies, clinical guidelines, and policy documents to examine determinants of unintended pregnancy among midlife women, with particular attention to health system and regulatory contexts in Indonesia. The review identifies biological uncertainty during perimenopause, reduced contraceptive vigilance, limited access to long-acting reversible contraception, and insufficient age-responsive counseling as key drivers of unintended pregnancy in midlife. In Indonesia, these risks are compounded by weak integration between reproductive health services and chronic disease management, as well as regulatory ambiguity following recent legal reforms. Based on this synthesis, the article proposes a three-tier prevention framework encompassing primary prevention (fertility awareness and contraceptive counseling), secondary prevention (early pregnancy detection and risk assessment), and tertiary prevention (timely, rights-based clinical management for medically complex pregnancies). Unintended pregnancy in midlife is not an exceptional event but a structurally produced public health issue shaped by interactions between biological, behavioral, health system, and policy factors. Addressing this challenge requires a life-course approach that integrates reproductive health with chronic disease care and aligns clinical practice with coherent, age-responsive policy frameworks to improve maternal health outcomes and reproductive autonomy.